Pengaruh Penerapan Model Team Games Tournament (TGT) Terhadap Hasil belajar Peserta Didik pada Materi Sejarah Kebudayaan Islam - Ummah, Aliffa Tul; Wirdati, Wirdati (An-Nuha, 2025)
This research is motivated by the management of PAI learning conditions which are still monotonous, the lack of variation in the learning process makes learning uninteresting so that impact on low student learning outcomes. Therefore, this study to determine the effect of using the Team Games Tournament (TGT) Model on learning outcomes in the Cultural History material. The research from this study uses a quasi-experimental method with a quantitative approach to test the effect of using the Team Games Tournament (TGT) Model on student learning outcomes. The sample of this study consisted of 60 people taken by purposive sampling from the existing population, namely class X as many as 396 students. The instrument used was a Learning Outcome Test. The data analysis technique used the Normality, Homogeneity, Simple Linear Regression and Hypothesis tests analyzed using SPSS software version 29. The results of this study indicate that there is an effect of using the Team Games Tournament (TGT) model on learning outcomes in the Cultural History material. The influence test using the Independent sample t-test obtained a significance of 0.001, which is less than the significance level of 0.05, so H0 is rejected and Ha is accepted. The conclusion is that the Team Games Tournament (TGT) Model has an effect on improving students' learning outcomes in the material of Islamic Cultural History.